Metode Dan Strategi Pengajaran Membaca pada Pembelajaran Bahasa Arab Bagi Pemula - Sitti Aisyah Chalik (Jurusan Pendidikan Bahasa Arab, 2020)
This paper discusses the methods and strategies of reading in Arabic lessons. As is well known that language skills include four aspects, namely speaking skills, writing skills, reading skills, and listening skills. At the beginner level, reading is a basic skill that must be mastered by everyone who wants to learn Arabic as a foreign language and as is well known that Arabic is a Foreign Language for non-Arabs. Teaching Arabic which is a foreign language requires various methods and strategies appropriate so that learning objectives can be achieved effectively and efficiently.